2017
DOI: 10.1080/21691401.2017.1345925
|View full text |Cite|
|
Sign up to set email alerts
|

Watercress-based electrospun nanofibrous scaffolds enhance proliferation and stemness preservation of human adipose-derived stem cells

Abstract: The present study describes the effects of Watercress extract (WE) based electrospun nanofibrous mats on the regulation of adhesion, proliferation, cytoprotection and stemness preservation of adipose-derived stem cells (ADSCs). Watercress (Nasturtium officinale) is one of the most important medicinal plant with a board spectrum of biological functions. For this purpose, WE-loaded PCL-PEG nanofibers were fabricated by electrospinning and characterized using FE-SEM and FTIR. Adhesion, proliferation and cytoprote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 47 publications
(19 citation statements)
references
References 51 publications
0
19
0
Order By: Relevance
“…These nanofibers are biocompatible, biodegradable, highly porous, and possess high surface‐to‐volume ratio. They can as well be implanted into tumors for local drug delivery (Dadashpour et al., ). Our finding indicated that 17‐AAG and 17‐DMAG‐loaded PCL/PEG nanofibers are more effective than the free drugs against lung and breast cancer cells.…”
Section: ‐Aag‐loaded Nanocarriersmentioning
confidence: 99%
“…These nanofibers are biocompatible, biodegradable, highly porous, and possess high surface‐to‐volume ratio. They can as well be implanted into tumors for local drug delivery (Dadashpour et al., ). Our finding indicated that 17‐AAG and 17‐DMAG‐loaded PCL/PEG nanofibers are more effective than the free drugs against lung and breast cancer cells.…”
Section: ‐Aag‐loaded Nanocarriersmentioning
confidence: 99%
“…The sensitivity of cells towards their local environment demands scaffold designs for tissue engineering that optimally mimic the natural extracellular matrix (ECM) [9]. Electrospun nanofibres have gained great interest during the last decade especially as substrates for both tissue engineering and regenerative medicine [10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the self‐renewal activity and plasticity extension of stem cells to several lineages, the elucidation of both in vivo and in vitro factors controlling multipotential properties is required to improve the basic knowledge of stem cells biology for providing large enough quantity of cells and further therapeutic manipulation (Saei Arezoumand et al ., ; Dadashpour et al ., ).…”
Section: Stem Cells Characteristics At a Glancementioning
confidence: 97%